Physical fitness of short-statured girls in pubertal age Sprawność fizyczna niskorosłych dziewcząt w wieku okołopokwitaniowym - Renata Czarniecka; Katarzyna Milde; Paweł Tomaszewski (Termedia Publishing House, 2011)
Introduction: Objective evaluation of physical fitness during adolescence is of importance in a school practice. Low body height may decide of unequal chances of short-statured youth as compared to other pupils performing physical fitness test. Aim of the study: To assess physical fitness of short-statured girls aged 13-16. Material and methods: 20 short-statured girls (body height below 10th percentile) from the province of Lodz aged 13-16 (15.1±0.9) years took part in the study. Their body height and body mass were 143.0±10.7 cm and 44.7±9.2 kg, respectively. Physical fitness was assessed with the use of EUROFIT test battery. The results were standardised against the functions of means and standard deviations for age computed for the Polish population and compared with the t-test. Results: As compared to girls from a general population, a short-statured one performed significantly worse with respect to two tests: SAR (sit-and-reach) and SBJ (standing board jump; p <0.01). In other fitness tests the results obtained were similar. It was also found that body height correlated positively and body mass negatively with general physical fitness. Conclusions: In order to compensate deficiencies in physical fitness of short-statured girls, particular attention should be paid to shaping those abilities in which they performed worse. On the other hand, changing the attitude towards evaluation in physical education should be also considered as to make it adequate to somatic possibilities of short-statured pupils and thus motivate them to undertake physical activity.